Health information design: envisioning and creating new ways of caring - Goldchmit, Sara Miriam (InfoDesign, 2024)
Advances in the past few decades have led to a radical transformation in how healthcare systems, communities, and individuals approach the concepts of well-being, health, and disease. Today, it is possible to access an infinite amount of data with the potential to diagnose, predict, prevent, and personalize disease treatment. The digital transformation generates a huge demand for the development and management of health information systems. At the same time, effective communication of medical information is one of the critical points for the person-centred care approach, to generate value and reduce waste. In the face of complex social challenges, interprofessional collaboration between design and health is already seen as indispensable. With the aim of contributing to the debate on information design for health in Brazil, this paper presents an overview of the area, discusses the current challenges of the health sector and the synergies with information design. It concludes that participatory approaches, performance evaluations and a greater link between information design and service design are important for the creation of more sustainable collaboration strategies between the areas, to increase the social impact of design research in Brazil.